Factors Affecting Credit Demand at Pegadaian Companies - Karnain, Bambang; Sugiharto, Sugiharto; Dewi, Rina; GS, Achmad Daengs (Jurnal Ekonomi, 2024)
This research aims to determine the factors that influence credit demand at Perum Pegadaian. This research method is literature study. The data analysis technique is by collecting information from various sources in fields related to the factors that influence the demand for credit at Perum Pegadaian, the data is collected and analyzed and conclusions are drawn. The results of this research state that the factors that influence the demand for credit at Perum Pegadaian include (1) customer's income level, (2) customer's education level (3) interest rate (4) service at Perum Pegadaian and (5) credit repayment period.